The peculiarities of growth of Cichorium intybus seed plants depending on mineral nutrition - Миколайко, В. П. (Scientific Progress & Innovations, 2016)
The results of studies of the influence of mineral nutrition on roots establishment, plant density in a phase of full growth, plant height and number of shoots have been highlighted. It was stressed that the use of complex of agricultural measures provided high root establishment, which ranged from 89,4 to 93,8 %. The high root establishment ensured optimal seed density, which is close to the planned one. It was found that the increase of Cichorium intybus height depended both on mineral fertilizers, schemes of its planting, and on the drip irrigation. It was mentioned that the use of fertilizers, especially nitrogenous and potassium N45 K70 has provided the largest increase in plant height and formation of shoots of first and second order as in control – without irrigation, as well as in drip irrigation.